Circulating vascular endothelial growth factor and cancer risk: A bidirectional mendelian randomization - Wu, Hong; Ma, Tianjun; Li, Dongli; He, Mei; Wang, Hui; Cui, Ying (Frontiers in Genetics, 2022)
In observational studies, circulating vascular endothelial growth factor (VEGF) has been reported to be associated with certain types of cancer. The purpose of this study was to verify whether there is a causal relationship between circulating VEGF and different types of cancer and the direction of the causal relationship. Summary statistical data were obtained from the corresponding genome-wide association studies (GWASs) to investigate the causal relationship between circulating VEGF and the risk of several cancers, including breast cancer, ovarian cancer, lung cancer, colorectal cancer, anus and anal canal cancer, prostate cancer, esophageal cancer, kidney cancer, bladder cancer, thyroid cancer, malignant neoplasm of the brain and malignant neoplasm of the liver and intrahepatic bile ducts. A two-sample bidirectional Mendelian randomization (MR) analysis and sensitivity tests were used to evaluate the validity of causality. A causal relationship was detected between circulating VEGF and colorectal cancer (OR 1.21, 95% CI 1.11–1.32, P< 0.000) and colon adenocarcinoma (OR 1.245, 95% CI 1.10–1.412, P< 0.000). Suggestive evidence of association was detected in VEGF on malignant neoplasms of the rectum (OR 1.16, 95% CI 1.00–1.34, P= 0.049). No causal relationship was found between circulating VEGF and other types of cancer, nor was there a reverse causal relationship from tumors to VEGF (P > 0.05). Circulating VEGF has a causal relationship with specific types of cancer. Our findings highlight and confirm the importance of circulating VEGF in the prevention and treatment of colorectal cancer.